Pengembangan LKPD Berbasis Discovery Learning Untuk Meningkatkan Minat Belajar IPAS Kelas V Sekolah Dasar - Tiara Junita Mukhtar; Vini Wela Septiana (PT Suria Academic Press, 2026)
. Student Worksheets (LKPD) are teaching materials that serve as learning guides for students in conducting structured and independent learning activities. The Discovery Learning model emphasizes the process of student concept discovery through the stages of stimulation, problem identification, data collection, data processing, verification, and conclusion drawing. Learning interest is a crucial factor influencing student success in the learning process. In elementary school Natural and Social Sciences (IPAS) instruction, learning interest serves as a motivator for students to actively engage in learning activities, such as observing, asking questions, discussing, and summarizing the material. This research falls under the Research and Development (R&D) category. The primary objective of this development is to develop a learning guide, namely a Discovery Learning-based LKPD. The development model used by the researchers is the ADDIE model. Based on the results of the LKPD validity evaluation involving expert assessment of the content, design, and language aspects, an overall score of 83% was obtained. Based on the results of the assessment of the material, appearance, and language aspects, the Discovery Learning-based LKPD obtained an average score of 95%. From the effectiveness aspect, the Discovery Learning-based LKPD was categorized as very effective. The effectiveness assessment was carried out through questionnaire analysis and student test results, with an overall score reaching 87%.